The Nationwide Health Information Network: The Case of the Expansion of Health Information Exchanges in the United States. Issue 4 (October 2018) - Ruley, Morgan; Walker, Victoria; Studeny, Jana; Coustasse, Alberto
Abstract : The Nationwide Health Information Network (NHIN) implemented secure exchange of health records through utilization of the Internet. The NHIN has greatly assisted in achieving the goals of the Health Information Technology for Economic and Clinical Health Act by promoting the adoption of Meaningful Use. Epic introduced a Health Information Exchange platform, Care Everywhere, which has facilitated Health Information Exchange availability. The purpose of this research was to determine the impact of NHIN and Epic Care's Care Everywhere on health care to determine whether their use in the emergency department (ED) has increased. The methodology for this study utilized a literature review. Twenty-eight sources were referenced for this study. With the NHIN implementation, repeated visits were decreased, visit times became faster, and charges were lower. Emergency department reported significant benefits with sharing clinical information. The NHIN implementation throughout the ED has increased the quality of health care; duplicated tests and drug usage were determined, and a reduction of the ED length of stay was also achieved.